Dinamika Aktor dalam Perumusan Kebijakan Desa Layak Anak - Sulistiowati, Rahayu; Prihantika, Ita; Atika, Dewie Brima; Choirunisa, Nabila (Jurnal Analisis Sosial Politik, 2020)
This article aims to describe the process of setting a child-friendly policy agenda at the local level in a child-friendly policy. Taking a case study in Panggunrejo Village, Pringsewu Regency, Lampung, Indonesia, this study found that policy issues and problems at the local level were still dominated by decisions from above. Local actors have not fully realized the importance of issues of violence against children as a priority agenda. In the field, even though the local Panggungrejo government as the main actor has strong legitimacy, its knowledge and expertise in the issue of child-friendly policies are lacking. An important actor in this policy is L-PAMAS has sufficient knowledge and expertise but does not have power in the policy setting agenda process. The dominant policy dynamism is played by L-PAMAS as a Non Governmental Organization which is involved in the formulation of child-friendly policies in Panggungrejo Village.